Universal Coverage of Hypertension Treatment Services in Malaysia Is Still an Elusive Goal - Chiu-Wan Ng; Mohd Ridzwan Shahari; Jeevitha Mariapun; Noran Naqiah Mohd Hairi; Sanjay Rampal; Ajay Mahal (Taylor & Francis Group, 2017)
An analysis of population coverage of hypertension treatment services can be used to make inferences about the performance of primary care services within health systems. Malaysia, an upper middle-income country, has a well-established primary care system but one that favors rural populations and provision of services for maternal and child health and infectious diseases. Demographic factors including rapid aging, urbanization, as well as lifestyle changes characteristic of a modernizing society have led to an increase in noncommunicable diseases, including hypertension. In this article, we used data from a nationally representative household health survey to develop service coverage indicators for hypertension screening and treatment services. The age-standardized prevalence of hypertension was estimated to be 33.9% (95% confidence interval [CI], 33.9, 33.9). Only 39.0% (95% CI, 37.5, 40.6) of adults with hypertension had been diagnosed by a medical practitioner, 35.7% had been on treatment, and 9.6% had blood pressure controlled under treatment. The diagnosis, treatment, and controlled treatment coverage were higher for older persons compared to younger persons. There were no differences in the diagnosis and treatment coverage between urban and rural areas and between ethnic groups. However, controlled treatment coverage was higher among Chinese and those living in urban areas. Our findings suggest that primary care services in Malaysia may need to intensify health education activities to promote screening services. There is also a need to reprioritize activities to provide regular community health screening of adults and increase access to affordable primary care services, especially in the urban areas.